HISTOPATHOLOGY OF RAT LIVER EXPOSED TO LEAD HEAVY METAL - Karina, Elisabeth; Berata, I Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
Lead is one of the most dangerous air pollutants.  Lead toxicity can have a severe impact, one of which is on the liver.  The purpose of this research was to determine the liver histopathology of rats exposed to lead at different doses.  This study used white rats of the Wistar strain, 2 months old and weighing 250-300 g.  The rats used were 20 given four treatments, control (P0), 0.5 ppm Pb acetate (P1), 1.0 ppm Pb acetate (P2), and 2.0 ppm Pb acetate (P3) for 30 days.  On day 31, a necropsy was performed and the liver was removed and put into 10% neutral buffered formalin.  After the liver was fixated, histopathological preparations were made using Hematoxylin and Eosin.  Histopathological examination staining with three variables measured, which were congestion, fatty degeneration, and necrosis.  The severity of the lesions was scored as 0, 1, 2, and 3 which could cause normal, mild, moderate, and severe lesions.  The data was then analyzed using the Kruskal-Wallis and Mann-Whitney non-parametric tests.  The result of this research showed that the administration of lead containing 0.5 ppm, 1.0 ppm, and 2.0 ppm had an effect on the histopathology of the liver of rats lesions as significant congestion and necrosis compared to controls, except for fatty degenerating lesions.